Sulodexide Protects Renal Tubular Epithelial Cells from Oxidative Stress-Induced Injury via Upregulating Klotho Expression at an Early Stage of Diabetic Kidney Disease - Yu Ning Liu; Jingwei Zhou; Tingting Li; Jing Wu; Shu Hua Xie; Hua-feng Liu; Zhangsuo Liu; Tae Sun Park; Yaoxian Wang; Wei Jing Liu (Journal of Diabetes Research)
The hypoalbuminuric effect of sulodexide (SDX) on diabetic kidney disease (DKD) was suggested by some clinical trials but was denied by the Collaborative Study Group. In this study, the diabetic rats were treated with SDX either from week 0 to 24 or from week 13 to 24. We found that 24-week treatment significantly decreased the urinary protein and HAVCR1 excretion, inhibited the interstitial expansion, and downregulated the renal cell apoptosis and interstitial fibrosis. Renoprotection was also associated with a reduction in renocortical/urinary oxidative activity and the normalization of renal klotho expression. However, all of these actions were not observed when SDX was administered only at the late stage of diabetic nephropathy (from week 13 to 24). In vitro, advanced glycation end products (AGEs) dose-dependently enhanced the oxidative activity but lowered the klotho expression in cultured proximal tubule epithelial cells (PTECs). Also, H2O2 could downregulate the expression of klotho in a dose-dependent manner. However, overexpression of klotho reduced the HAVCR1 production and the cellular apoptosis level induced by AGEs or H2O2. Our study suggests that SDX may prevent the progression of DKD at the early stage by upregulating renal klotho expression, which inhibits the tubulointerstitial injury induced by oxidative stress.